Removal of basic nutrients from the soil by field crop rotations with different fertilizers - Hospodarenko, Н. M.; Cherno, O. D.; Martyniuk, A. T.; Boiko, V. P. (AgroChemistry and Soil Science, 2021)
The effect of application of different doses and combinations of mineral fertilizers in field crop rotation on the content of basic nutrients in plants, economic and relative removal of winter wheat, corn, spring barley and soybeans was studied. Soil - Luvic Chernic Phaeozem. The scheme of the experiment includes 11 variants of combinations and separate application of mineral fertilizers and, including the variant without fertilizer. It was found that the level of nitrogen content of easily hydrolyzed compounds in the soil significantly affects its content in the grain of spring barley, corn, soybeans (R2 = 0,92–0,93), less - winter wheat (R2 = 0,63). The content of mobile phosphates in the soil has almost the same effect on its content in the main and non-commodity part of the crop, regardless of the crop (R2 = 0,39–0,70). The smallest relationship between the content of mobile compounds in the soil and in the crop was in potassium, but in soybean seeds and straw of spring barley and soybeans it was clearly traced (R2 = 0,53–0,68). Nitrogen (64,4–149,9 kg / ha) has the largest share in the economic extraction of nutrients with grain and seed yield, followed by phosphorus – 21,1–51,4 kg P2O5/ ha, depending on the crop. On the formation of the crop unit of marketable and the corresponding amount of non-marketable crop products absorb nutrients in the following ratio N : P2O5 : K2O: winter wheat – 1 : 0,4: 0,7; corn – 1 : 0,3 : 0,8; spring barley – 1 : 0,4 : 0,7 and soy – 1 : 0,4 : 0,4. With the non-commodity part of the crop, nitrogen with corn stalks returns to the soil from economic removal – 28–36 %, phosphorus with soybean straw (47–54 %) and potassium with winter wheat straw and corn stalks – 74–80 %, depending on the experiment variant.